2020
DOI: 10.20448/journal.501.2020.71.15.24
|View full text |Cite
|
Sign up to set email alerts
|

Nexus between Foreign Remittances and Economic Growth in Nigeria: Role of the Financial Sector

Abstract: In recent times, the economic growth literature is becoming more interested in the macroeconomic impacts of foreign remittances. This focus could be because foreign remittances now constitute the largest source of foreign capital flows for developing countries next to foreign direct investment (FDI). To this end, the present study analyzed the possible role of the financial sector in the nexus between foreign remittances and economic growth in Nigeria over the period of 1981 to 2015. To circumvent the possible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 24 publications
(46 reference statements)
1
5
0
Order By: Relevance
“…In addition, the adjustment parameter or the coefficient on the error correction term (ECT) fulfils the convergence condition of being 15 Our results also paralleled the previous findings of Ramirez and Sharma (2008); Giuliano and Ruiz-Arranz (2009); Mundaca (2009); Dzansi and Shukur (2010); Bettin and Zazzaro (2011);Nyamongo, Misati, Kipyegon and Ndirangu, (2012); Lartey (2013); Chia (2014), andEl Hama (2016) while negating the findings of Chowdhury (2016). We also affirmed the findings of Garba, et al (2020) that there are both complementarity and substitutability effects of remittances and financial sector development on economic growth via the investment channel. Similarly, Adeniyi, et al, (2017) revealed that the complementarity or substitutability effect of remittances and financial development on output volatility depends on the indicators of financial development used.…”
Section: Regression Results and Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…In addition, the adjustment parameter or the coefficient on the error correction term (ECT) fulfils the convergence condition of being 15 Our results also paralleled the previous findings of Ramirez and Sharma (2008); Giuliano and Ruiz-Arranz (2009); Mundaca (2009); Dzansi and Shukur (2010); Bettin and Zazzaro (2011);Nyamongo, Misati, Kipyegon and Ndirangu, (2012); Lartey (2013); Chia (2014), andEl Hama (2016) while negating the findings of Chowdhury (2016). We also affirmed the findings of Garba, et al (2020) that there are both complementarity and substitutability effects of remittances and financial sector development on economic growth via the investment channel. Similarly, Adeniyi, et al, (2017) revealed that the complementarity or substitutability effect of remittances and financial development on output volatility depends on the indicators of financial development used.…”
Section: Regression Results and Discussionsupporting
confidence: 87%
“…On the other hand, Kousar, Rais, Mansoor, Zaman, Shah and Ejaz (2019) discovered that remittance raises poverty level and income inequality while financial development has a positive impact on poverty reduction and income inequality in Pakistan. Further, Olaniyan (2019) and Garba, et al, (2020) tested the validity of the complementarity and substitutability hypotheses in Nigeria using generalized methods of moment and two-stage least square (2SLS) methods, respectively. These studies revealed that remittances had negative effect on economic growth but enhance economic growth when interacted with financial development indicators, particularly liquid liabilities, private sector credit and total bank deposits.…”
Section: Empirical Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…The more open the economy is to the rest of the world, the higher the inflow of remittances passing through the financial market. Second, previous studies in Nigeria (Anetor, 2019; Olaniyan, 2019; Garba et al , 2020) appear to have focused on domestic financial development using single variables such as M 2 as share of GDP and bank credit to private sector as measures of financial development. On this premise, this study focuses on financial openness.…”
Section: Introductionmentioning
confidence: 99%